"Peran Mahasiswa KKN UNP dalam Mengedukasi Siswa Sekolah Dasar tentang Bahaya Bullying: Studi Kasus di SD 12 Sapan, SD 13 Sungai Durian, dan SD 02 Sapan, Kelurahan durian 2, Kecamatan Barangin,Kota Sawahlunto" - Irfan Oktavianus; Azetria Rahmadani; Fahrozid Abelno; Fauzia Annisa Isfa; Hafizah Tulaini; Muhammad Arvi; Rashinta Dwiananda Puteri; Silvi Tamara (Jurnal Bintang Pendidikan Indonesia, 2024)
Bullying is a harmful behavior that has the potential to cause serious psychological impacts on children, especially in school settings. This study aims to explore the role of Universitas Negeri Padang (UNP) Student Community Service (KKN) students in educating elementary school students about the dangers of bullying. Socialization activities were conducted in three elementary schools, namely SD 12 Sapan, SD 13 Sungai Durian, and SD 02 Sapan, Durian 2 Village, Barangin District, Sawah Lunto City, using presentation and interactive discussion methods. The results showed that 55% of students considered bullying as a joke, with the most common form of bullying being teasing about parents' names and physical conditions. These findings indicate the need for continuous education to increase students' understanding of the boundaries between joking and bullying and its negative impacts. Through this program, UNP KKN students contribute to creating a safer and more supportive environment for elementary school students.